Correlation Between Knowledge Management Maturity and Organizational Excellence: An exploratory study of the perspectives of a representative sample of administrative and academic leaders at Duhok Polytechnic University. - Ibrahim, Omid; Shaban, Farsat; Khader, Shehab (Humanities Journal of University of Zakho, 2021)
This study aims to determine the correlation between Knowledge Management Maturity and Organizational Excellence at Duhok Polytechnic University by employing a five-Stage Knowledge Management Maturity Model: (Initial, Awareness, Defined, Managed, and Optimized). The study is grounded on three hypotheses that arose from the question: Is there a correlation between Knowledge Management Maturity and Organizational Excellence? The study's significance is demonstrated by addressing the study's question and hypotheses to raise awareness of the study and serve as a springboard for the researched university's pursuit of Organizational Excellence. The theoretical part of the study was developed based on the available literature. Field data were collected using an electronic questionnaire form. The total number of administrative leaders who responded was (69). The study arrived at several conclusions by statistical processes, the most notable of which are as follows: There is a substantial correlation between levels of Knowledge Management Maturity and Organizational Excellence. The study made some recommendations, the most significant of which are as follows: The researched university in particular and other universities should focus on the concept of knowledge management maturity and the applied steps it includes as a strategy to achieve organizational excellence, due to the emergence of a moral and positive correlation between the two concepts .